A fast algorithm for multiple elimination and transmission compensation in primary reflections. Issue 1 (7th January 2020) - Zhang, Lele; Slob, Evert
SUMMARY: The transmission compensated primary reflections can be obtained from the single-sided acoustic reflection response in the two-way traveltime domain. This is achieved by eliminating free-surface and internal multiple reflections and compensating for transmission losses in primary reflections without model information. The substantial computational cost of the proposed scheme can be reduced by an order of magnitude with a fast implementation version. This is achieved by using the previously computed filter functions as initial estimate for every new truncation time value. We evaluate the success of the scheme with simple and complex 2-D numerical examples. We find that the scheme has excellent performance in most cases, except for the case where strong reflectors are present. In such case, the current scheme suffers from lack of convergence.